LATENT CLUSTER ANALYSIS OF INSTRUCTIONAL PRACTICES REPORTED BY HIGH- AND LOW-PERFORMING MATHEMATICS TEACHERS IN FOUR COUNTRIES - Cheng, Qiang; Hsu, Hsien-Yuan (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2017)
Using Trends in International Mathematics and Science Study (TIMSS) 2011 eighth-grade international dataset, this study explored the profiles of instructional practices reported by high- and low-performing mathematics teachers across the US, Finland, Korea, and Russia. Concepts of conceptual teaching and procedural teaching were used to frame the design of the current study. Latent cluster analysis was applied in the investigation of the profiles of mathematics teachers’ instructional practices across the four education systems. It was found that all mathematics teachers in the high- and low-performing groups used procedurally as well as conceptually oriented practices in their teaching. However, one group of high-performing mathematics teachers from the U.S. sample and all the high-performing teachers from Finland, Korea, and Russia showed more frequent use of conceptually oriented practices than their corresponding low-performing teachers. Another group of U.S. high-performing mathematics teachers showed a distinctive procedurally oriented pattern, which presented a rather different picture. Such results provide useful suggestions for practitioners and policy makers in their effort to improve mathematics teaching and learning in the US and in other countries as well.DOI: http://dx.doi.org/10.22342/jme.8.2.4066.115-132